The Effect of Experiential Learning Viewed From Gender Differences Perspective toward Physics Learning Outcome - Nurfadilah Nurfadilah (Jurnal Pendidikan Fisika, 2019)
This research was a quasi-eksperiment by using nonequivalent control group design and factorial design 2x2. It was conducted in class X-1 and X-2 of senior high school 1 of Takkalalla Wajo and aimed to: (1) analyse the difference of physics learning outcome between students who where taught with experiential learning and the ones who where taught conventionally; (2) analyse the difference of physics learning outcome between male students who where taught with experiential learning and the ones who where taught conventionally; (3) analyse the difference of physics learning outcome between female students who where taught with experiential learning and the ones who where taught conventionally; (4) analyse the interaction between learning models (experiential and conventional laerning) and gender (male and female students) toward the achievement of students physics learning outcome. The collection of data carried out before the use of experiential learning in class experiments and conventional in the control class in order to determine whether different initial knowledge of students (pre-test), and the results for the experimental class to learn physiscs of controls didn’t differ significantly. Thus the hypothesis test conducted after the second execution after the learning by giving the final test (post-test) was used parametric test. The results of hypotheses testing that used two-way variance analysis with SPSS 16 showed that (1) there was difference of physiscs learning outcomes significantly between students with experiential learning and conventionally; (2) there are differences in learning outcomes were not significant among physics students with experiential learning and conventionally on male students; (3) there are differences in learning outcome were not significant among physics students with eksperiential learning and conventionally on female students; (4) there was no interaction between learning models (experiential and conventional laerning) and gender (male and female students) toward the achievement of students physics learning outcome.Keywords: experience, gender, learning outcomePenelitian ini merupakan penelitian eksperimen semu menggunakan desain penelitian nonequivalent control group design dan rancangan faktorial 2×2 yang dilaksanakan di kelas X-1 dan X-2 SMAN 1 Takkalalla Kabupaten Wajo dengan tujuan untuk; (1)menganalisis perbedaan hasil belajar Fisika siswa antara yang diajar melalui pembelajaran berdasarkan pengalaman dan secara konvensional, (2)menganalisis perbedaan hasil belajar Fisika siswa antara yang diajar melalui pembelajaran berdasarkan pengalaman dan secara konvensional untuk laki-laki, (3)menganalisis perbedaan hasil belajar Fisika siswa antara yang diajar melalui pembelajaran berdasarkan pengalaman dan secara konvensional untuk perempuan, dan (4)menganalisis interaksi antara pembelajaran (berdasarkan pengalaman dan secara konvensional) dengan gender (siswa laki-laki dan perempuan) terhadap pencapian hasil belajar Fisika siswa. Pengumpulan data dilaksanakan sebelum digunakan pembelajaran berdasarkan pengalaman dikelas eksperimen dan secara konvensional di kelas kontrol dengan tujuan untuk mengetahui berbeda tidaknya pengetahuan awal siswa (pre-test), dan diperoleh hasil belajar fisika untuk kelas eksperimen dan kontrol yang tidak berbeda secara signifikan. Dengan demikian uji hipotesis yang dilakukan setelah pelaksanaan kedua pembelajaran usai maka pemberian tes akhir (post test) digunakan uji parametrik. Hasil pengujian hipotesis yang dilakukan dengan analisis varians dua jalur dengan SPSS 16 yang menunjukkan bahwa (1)terdapat perbedaan hasil belajar fisika yang signifikan antara siswa dengan pembelajaran berdasarkan pengalaman dan secara konvensional, (2)terdapat perbedaan hasil belajar fisika yang tidak signifikan antara siswa dengan pembelajaran berdasarkan pengalaman dan secara konvensional pada siswa laki-laki, (3)terdapat perbedaan hasil belajar fisika yang tidak signifikan antara siswa dengan pembelajaran berdasarkan pengalaman dan secara konvensional pada siswa perempuan, dan (4)tidak terdapat interaksi antara pembelajaran (berdasarkan pengalaman dan secara konvensional) dengan gender (laki-laki dan perempuan) terhadap hasil belajar fisika siswa.Kata kunci: pengalaman, gender, hasil belajar